(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The hydrological forecasting methods that have been used for many years in Russia require precision input data, which are difficult to obtain. Until now, none of forecasting systems, developed by Russian hydrologists, has been officially implemented in practice. In the face of an increasing number of catastrophic and destructive hydrometeorological hazards, the development of a modern automated system for operational flash floods forecasting is highly relevant in Russia. In this paper, a new technological chain for background streamflow forecasting is presented. The authors have attempted to create such a chain under the conditions of the country’s poor hydrometeorological network and difficulties in obtaining data and their assimilation. The chain presents a joined logistic scheme, which was developed based on analytical elaboration of scientific works of key Russian hydrologists. The paper also includes the analysis of the most efficient use of the hydrometeorological data available through the national observation network. This seems to be assimilation of satellite and radar data, in situ observations, numerical weather prediction models and catchment models outputs.